Factors Influencing Individuals' Short-term Investment Intentions - Ferreira-Schenk, Sune; Dickason-Koekemoer, Zandri; Shah, Naveed Hussain (International Journal of Economics and Financial Issues, 2021)
This article aimed to determine what drives investors short-term intention to invest following a more sociological and behavioural approach by including investor personality traits, behavioural finance biases these investors could be subject towards, and their risk tolerance behaviour. Based on the complexity of the variables a multivariate statistical approach was preferred. Therefore, a structural equation model (SEM) was employed and proved to be a good model for the data. Secondary data was obtained from a pre-collected survey by a private investment firm for research purposes. The results indicated that investors who have strong extraversion, agreeableness and openness to experience personality traits will be more likely to invest in short-term investment portfolios. From the nine behavioural finance biases, one bias significantly explained investors short-term investment intentions. Investors who are overconfident in their investment skills tend to invest more in the short-term. It is therefore recommended to portfolio management companies that several sociological and behavioural variables do explain whether investors will be willing to invest in short-term or more long-term investment portfolios. Keywords: risk tolerance, behavioural finance biases, personality traits, short-term investment JEL Classifications: A14, G11, G41 DOI: https://doi.org/10.32479/ijefi.11449